Physiological factors affecting the mechanical performance of peripheral muscles: A perspective for long COVID patients through a systematic literature review - Rao, H. R. S.; Hamzaid, N. A.; Ahmad, M. Y.; Hamzah, N. (Frontiers in Physiology, 2022)
Background: Peripheral muscle weakness can be measured quantitatively in long COVID patients. Mechanomyography (MMG) is an alternative tool to measure muscle strength non-invasively.